Further Insights into the Mechanisms and Clinical Implications of Run-Mu-Ling Granules in Dry Eye Disease [Letter] - Wei W; Gao H; Guo X; Chen C (Journal of Inflammation Research)
Wei Wei,1 Haoming Gao,2 Xiuli Guo,2 Chen Chen3 1Armed Police Force First Mobile Corps Hospital, Baoding, Hebei Province, People’s Republic of China; 2People’s Liberation Army 32183 Troops Hospital, Baicheng, Jilin Province, People’s Republic of China; 3Department of Ophthalmology, Dalian Women and Children’s Medical Group, Dalian, Liaoning Province, People’s Republic of ChinaCorrespondence: Chen Chen, Department of Ophthalmology, Dalian Women and Children’s Medical Group, 154 Zhongshan Road, Xigang District, Dalian City, Liaoning Provinve, People’s Republic of China, Email chenchenkaoyan2008@163.com